PKM Pelatihan Dan Pendampingan Guru-Guru Di Sekolah Dasar Negeri 36 Manado Untuk Pengembangan Media Presentasi Digital Menggunakan AI Designer Tool: Training and Mentoring PKM Program for Teachers at State Elementary School 36 Manado for the Development of Digital Presentation Media Using AI Designer Tools (Tumou Tou: Jurnal Pengabdian Masyarakat, 2025)
Sekolah Dasar Negeri 36 Manado is one of the elementary schools located in the Malalayang District of Manado City. Furthermore, Sekolah Dasar Negeri 36 Manado has become a favourite in the Malalayang district area. The challenges faced by Sekolah Dasar Negeri 36 include a significant number of students and the need for improvements in the learning system innovation. The purpose of this training activity is to provide insight, knowledge, and new competencies to the teachers of Sekolah Dasar Negeri 36 Manado in designing and delivering teaching materials. Before the training, a pre-test is conducted to assess the initial abilities of the training participants. The training continues with coaching and mentoring processes. After the training, participants are given a post-test to determine to what extent they have absorbed and implemented the training materials provided. It was found that, in general, there was an improvement of 20% to 75% for each competency as reflected in each question in the pre-test and post-test